EDITORIAL - Kochumuttom, Thomas (Journal of Dharma, 1980)
The Guru, one of the oldest religious institutions, is one of the central themes in the contemporary religious discourses. Similarly, although the concept of authority, religious or otherwise, is being reinterpreted, if not rejected, the authority of a Guru seems to be getting more and more established in the contemporary world. Again, although a sense of religious indifference is apparent in the technologically developed countries, the Gurus of today are attracting larger and larger followings even in those countries. These observations indicate man’s undying enthusiasm for Gurus, and something like a perennial interest for them. This is sufficient justification for devoting the present number of our journal to a study of Gurus, Spiritual Guides.